A BODIPY‐Hemicyanine‐Based Water‐Soluble Dual‐Color Fluorescence Probe for Colorimetric Monitoring of Intracellular Endogenous Sulfur Dioxide and Bioimaging Applications. Issue 10 (11th March 2020) - Liu, Ying; Wu, Yong‐Xiang; Zhang, Dailiang; Xi, Yang; Yu, Shengrong; Zhong, Hongmei; He, Kangdi; Li, Dian; Wei, Wen‐Ting; Cao, Yuting; Gan, Ning
Abstract: We conjugated aldehyde‐BODIPY with the water‐soluble iodopropionic‐acid‐hemicyanine to develop a new dual‐color fluorescence probe (BHC) for selective and sensitive monitoring of endogenous SO2 for the first time. Through excellent water solubility and the unique nucleophilic addition reaction, BHC has a higher selectivity for the colorimetric monitoring of SO2 than other related substances. The resulting probe BHC has red emission, and can be converted to green emission after reacting with SO2 . Then the dual‐color fluorescence probe was further applied to image intracellular endogenous generated SO3 2− /HSO3 − by the metabolism of living cells with satisfactory results. This strategy provides a new tool for revealing the metabolism of SO3 2− /HSO3 − and quantifying their distribution in living cells. Abstract : Herein, we synthesized a bodipy‐hemicyanine‐based water‐soluble dual‐color fluorescence probe (BHC) for selective and sensitive monitoring of intracellular endogenous sulfur dioxide (SO2 ) by the nucleophilic addition reaction for the first time. The water‐soluble probe BHC has red emission, and can be converted to green emission after reacting with SO2 . Then the the dual‐color fluorescence probe was further applied to image generated SO3 2− /HSO3 − by the metabolism of living cells. This strategy provides the potential for revealing the distribution of SO3 2− /HSO3 − in living cells.